Improving The Methodology Of Solving Chemistry Problems On The Basis Of Interdisciplinarity (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The issue of methods and methods of interdisciplinary implementation of problem solving in chemistry is considered to be one of the general problems of improving the methods of teaching chemistry. Interdisciplinary integration serves to master the content of academic subjects by implementing it in future chemistry teachers in "Practical training of the science of chemical calculation" in pedagogical universities. At the same time, it is necessary to more fully determine the didactic possibilities of interdisciplinary integration, to determine their functions in teaching, and thus to support future chemistry teachers to effectively use interdisciplinary integration in the teaching process